Pengaruh Model Pembelajaran Think Talk Write (TTW) Berbantu Media Gambar terhadap Hasil Belajar Kognitif dan Motivasi Belajar Siswa pada Materi Sistem Pernapasan Kelas VIII SMP Negeri 5 Kodi - Kaka Daha, Selviana; Budi Lestari, Purwaning (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2018)
Good student learning outcomes, one of which is determined by student motivation is in terms of fostering passion, pleasure and enthusiasm. one of them is the selection of learning models that are in accordance with the characteristics of students and subject matter. TTW is a learning model that facilitates verbal training orally and writes the language smoothly. The learning model encourages students to think, speak, and then write a particular topic. aims to find out whether there is influence of Think Talk Write (TTW) assisted learning media images on cognitive learning outcomes and student motivation on respiratory system material class VIII SMP Negeri 5 Kodi Academic Year 2017/2018. This type of research is quasi experimental using the pretest postest desing research design. Population in even semester. This research sample consists of 2 classes, namely class VIII A as many as 30 students as an experimental class and class VIIIB as many as 30 students as a control class. Data analysis techniques use normality test, homogeneity test and hypothesis testing using the Anacova test at a significant level of 5%. Based on the results of the study showed that the average learning outcomes of students who obtained learning with Think Talk Write assisted learning models of media images obtained an average of 80.86 while the average learning outcomes of students who did not use media-based Think Talk Write learning models were obtained flat 73.96. The conclusion of the study is that there is an influence of students' understanding that is taught by using the media-assisted Think Talk Write (TTW) learning model with learning without using a model (0,000